SUMBER-SUMBER HUKUM ISLAM DAN IMPLEMENTASINYA: Kajian Deskriptif Kualitatif Tentang Al-Qur’an, Sunnah, dan Ijma’ - Muannif Ridwan; M. Hasbi Umar; Abdul Ghafar (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The sources of Islamic law are anything that gives birth to legal provisions governing Muslims. It has been agreed by scholars that the Qur’an is the main source of law for Muslims, the next is hadith / sunnah, and ijma'. The Qur’an is an aggregate of all rules in any situation and condition for mankind. All aspects of human life are in it. Muhammad, PBUH. as an apostle and mukzijat al-Qur’an given the privilege to explain in detail things that are still general in the Qur’an. His explanation was not just utterance, but also inscribed with real deeds with full obedience. The words and deeds of the Messenger of Allah which are called hadiths clarify Islamic law, so that people who have faith will easily obey God's commands. As caliph on earth, humans are required to observe the commands contained in the two main sources of Islamic law, namely the Qur’an and the hadith. If there is no clear information about the latest issue in both, then the Qur’an and the hadith itself instruct the scholars to devote their thoughts to establishing the law, and the result of the accuracy is called ijma'. Thus ijma’ can be used as the third source of Islamic law. hence the Qur’an and the hadith itself which instruct the scholars to devote their thoughts to establishing the law, and the result of which is called ijma'. Thus ijma’ can be used as the third source of Islamic law, hence the Qur’an and the hadith itself which instruct the scholars to devote their thoughts to establishing the law, and the result of which is called ijma'. Thus ijma' can be used as the third source of Islamic law. This study uses a qualitative descriptive method with the type of research used is library research. The purpose of this research is that the reader knows the urgency of understanding the sources of Islamic law about al-Qur’an, Sunnah, and Ijma' and its comprehensive implementation, so that readers cannatural daily life can be motivated to practice religion according to its rules and find Islam to be a dynamic, humanist, elastic, and egalitarian religion as well as compatible (shalihun li kulliz zaman wal makan).